MOODLE: Ten years @ Universidade Portucalense. - Sobral, Sónia Rolland (2015)
Modular Object-Oriented Dynamic Learning Environment (MOODLE) was first used in Universidade Portucalense during the 2003-2004 academic year only with the presence of three courses, all responsibility of the administrators of the platform, members of the Computer science Department. Four years after, the administration of MOODLE became responsibility of Computing Services. In 2008 all the courses taught at the University Portucalense have presence in MOODLE, regardless of the willingness of responsible teachers. Between July 2006 and July 2013 the Rectory has promoted five MOODLE applied courses for teachers. At the beginning of each school year there is a reception to new teachers where they have also an introduction to this platform. Meanwhile there have been some upgrades in the platform, and in 2013/14, the university upgrade to the last version. Rounding up 10 years of MOODLE in Universidade Portucalense an evaluation of this use must be done as well as a picture of how teachers see the 2014 platform, and how they think this resource can improve students’ learning. Universidade Portucalense is a good mirror of Higher Education Institutions in Portugal as it is organized in four different departments and has several types of teachers: different scientific areas, ages, cultures and distinct technological skills. This study aims to find if teachers use MOODLE and how they do it to supplement classroom lessons, improving or contributing to student success, from the teachers’ perspective.